Analisis tingkat kesesuaian materi fisika SMA/MA dengan tujuan kurikulum - Luthfika Putri Antari; Ahmad Fauzi; Rifai Hamdi; Silvi Yulia Sari (Universitas Negeri Padang, 2020)
There are several processes in education, one of which is the curriculum. The curriculum is a tool to achieve educational objectives Without an appropriate and appropriate curriculum it will be difficult to achieve the educational goals and objectives to be achieved. As a useful tool for achieving a goal, the curriculum should be able to adapt to changing times and advances in science and the sophistication of technological developments. In 2013 the Indonesian government published a new curriculum called the 2013 curriculum to create a generation ready to face the challenges of the future. The purpose of the 2013 Curriculum itself is to prepare Indonesian people to have the ability to live as individuals who are faithful, productive, creative, innovative and affective citizens and are able to contribute to the life of society, nation, state and world civilization.Among the keys to success that determine the successful implementation of the 2013 Curriculum are learning facilities and resources. Thus, textbooks are still a very important source of learning for studentsMaterials or learning materials are basically the